Multivariate Optimization of Cephalexin, Ciprofloxacin, and Clarithromycin Degradation in Medical Laboratory Wastewater by Ozonation. (4th May 2022) - Basturk, Irfan; Varank, Gamze; Murat-Hocaoglu, Selda; Yazici Guvenc, Senem; Can-Güven, Emine; Oktem-Olgun, Elmas Eva; Canli, Oltan
ABSTRACT: In this study, the performance of the ozonation process was investigated in the removal of antibiotics (Cephalexin, Ciprofloxacin, and Clarithromycin) from medical laboratory wastewater. Central composite design, one of the response surface methodologies, was applied to optimize process parameters and to develop a mathematical model. Analysis of variance (ANOVA) was performed to analyze the data and obtain the interactions between the responses and process variables. Independent variables were initial pH, reaction time, and ozone dosage, while the responses were the removal of Cephalexin, Ciprofloxacin, and Clarithromycin. Statgraphics Centurion XVI.I software was used for developing the quadratic regression models in the estimation of removals. The determined correlation coefficients were very high for the removal of all three antibiotics and the model was sufficiently in good agreement with experimental results. The experimental removal fractions of Cephalexin, Ciprofloxacin, and Clarithromycin under optimum process conditions were 99.5%, 98.3%, and 99.6%, respectively. As a result of the study, it was determined that ozonation is an effective treatment method in antibiotic removal from medical laboratory wastewater and the central composite design is a convenient tool for process optimization.